Links between Tropical Cyclone Activity and Madden–Julian Oscillation Phase in the North Atlantic and Northeast Pacific Basins - Barrett, B.; Leslie, Lance (American Meteorological Society, 2009)
The leading intraseasonal mode of atmospheric and oceanic variability, the Madden–Julian oscillation (MJO), influences tropical and extratropical sea level pressure, temperature, divergent and rotational wind components, moisture, and deep convection. As a 40- to 50-day oscillation, the MJO is also known to influence tropical phenomena, including tropical cyclone (TC) activity in various TC basins. The links between the MJO and multiple measures of TC activity, including genesis, landfall, and an integrative accumulated cyclone energy (ACE) index, were quantified for multiple TC-formation basins across the Western Hemisphere, including the North Atlantic and northeast Pacific Ocean and subbasins, for the period 1978–2006. Using this relatively long (29 yr) TC dataset and employing an upper-tropospheric MJO diagnostic that is physically meaningful over the entire Western Hemisphere, this study extends existing research on the relationships between the MJO and TCs. The NOAA Climate Prediction Center’s operational MJO index, derived from 200-hPa velocity potential data, was divided into three phases. Relative frequencies of the MJO phases were compared with observed levels of TC activity using a binomial distribution hypothesis test. The MJO was found to statistically significantly modulate the frequency of TC genesis, intensification, and landfall in the nine TC basins studied. For example, when an MJO index was large and positive at 120°W, hurricanes and intense hurricanes were 4 times as likely to make landfall in the North Atlantic. This modulation of TC activity, including landfall patterns in the North Atlantic, was physically linked to the upper-atmospheric response to the eastward-propagating MJO and is evident as a dipole of TC activity between Pacific and Atlantic subbasins.